Physicochemical characterization of copper slag and alternatives of friendly environmental management - Sánchez M.; Sudbury M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Copper slags are usually considered a waste and characterized only by the final copper content. Large and increasing quantities are being produced and disposed of by stockpiling near the metallurgical plants. This paper stresses the importance of physico-chemical characterization when considering uses for slags and the possibility of recovering the valuable metals still remaining in this phase. The purpose of this work is to support and encourage a change in the classical perception of slag from a ‘waste’ to a ‘resource’; promote the development of new technologies for treatment to recover residual values and encourage a search for new uses; with the ultimate objective of eliminating slag stockpiles thereby diminishing the environmental impact of smelting operations. Some of the results of experimental laboratory work done by the authors and examples of commercial applications will be shown. A promising future for valorization and utilization of slags is expected and will provide an example when considering the use of all the other large quantities of wastes generated by the mining industry.